Pengaruh Pengetahuan Investasi, Kemudahan Teknologi, dan Kemampuan Keuangan Terhadap Minat Investasi Generasi Millennial Di Pasar Modal - Baruni, Fiegi; Priyastiwi (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
Investment is essential to a country growth and economic development. This study examines the effect of investment knowledge, technological convenience, and financial ability on investment interest in the capital market. The population in this study were active students of the undergraduate accounting study program at university in Yogyakarta. The sampling technique used in this research is purposive sampling or a purposive sample. The samples obtained according to the criteria were 92 respondents of 120 respondents. The data collection method used an online questionnaire. The data analysis technique used descriptive analysis, multiple linear regression, and interaction tests. The results of this study indicate that: Investment knowledge does not affect students interest in investing in the capital market. The ease of technology affects students interest in investing in the capital market. Financial ability affects students interest in investing in the capital market. Investment knowledge balanced with financial ability will increase student investment interest. Student investment interest will be higher if the high financial ability and ease of use of technology.